The time-travelling cat and the great Victorian stink - "Jarman, Julia" (London; Andersen Press, 2017)
Topher's amazing cat, Ka, has time-travelled again, leaving him yet another mysterious clue. Following his nose, Topher finds himself in Victorian London, where disease is rife and the Thames is clogged with stinking sewage! There, he discovers a plot to kill Joseph Bazalgette, who is trying to save the city. Determined to foil this foul plan, Topher must first escape from an arch-criminal and his den of thieves
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Fantasy/Magic Fiction